Jean-Marie Gustave Le Clézio et Patrick Modiano dans le champ intellectuel européen - Pilar Andrade Boué (Carnets)
This article compares the situation of two French Nobels, Le Clézio and Modiano, in the European literary field. The author deals first with the family and social capital, then with the topics treated in the books of both writers, as they slow or accelerate the path in the cursus honorum, finally with the promotional and media strategies needed to succeed.